Desarrollo de la práctica reflexiva en estudiantes de práctica pre profesional de educación inicial en la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Garcia Chavez, Ilmer Isabel (2022)
Determining the level of development of reflective practice in students of pre-professional practice of initial education at the Faculty of Education Sciences and Humanities of the National University of the Peruvian Amazon Iquitos in 2021 has been the main objective of the research, for this has been necessary to analyze the findings, which are presented in the results section. The research adopts the descriptive type with a field, univariate, and cross-sectional design. The population consisted of 85 students of pre-professional practice of initial education, who were also part of the sample. To obtain the data, a questionnaire was used, previously validated by experts and the survey technique was applied. The conclusion is that the level of development of reflective practice in students of pre-professional practice of initial education, in 74.1% is at the moderate level and in 25.9% at the high level.